[3+2] cycloaddition reactions of arylacetylenes with carbonyl ylides derived from 1-aryl-1-diazohexane-2,5-diones - Hodgson, D; Glen, R; Redgrave, A (2002)
The synthesis and 1,3-dipolar cycloaddition reactions of α-aryl-α-diazodiones with aryl acetylenes (up to 76% ee) are described. © 2002 Elsevier Science Ltd. All rights reserved.